Neoliberal and Post-Liberal Europe - Koljević Griffith, Bogdana N. (Sociološki pregled, 2019)
The issue of causes and effects of 1989 is considered as the question of development and effects of neoliberal Europe. It is argued that this is a process of loss of sovereignty and political subjectivity i.e., one of promotion of individualistic atomism and ideology of „human rights“ which, also, ends up in „humanitarian interventionism“. Binary set of relations between „totalitarianism“ and „democracy“ - as well as the following concept of „transition“ – secured the dominance of liberalism on practically all levels while from the geopolitical aspect this construct corresponded with US hegemony in Europe – best perceived on the example of the EU. Besides neoliberal, postmodern discourse had its own impact on these processes. In conclusion, equality, true democracy, and the return to the state are emphasized as the basis of post-liberal Europe of the 21st century.
Keywords: neoliberalism; sovereignty; political subjectivity; true democracy; Europe